Comparing the effects of smartphone-based and face-to-face education on the quality of life and coping skills among patients with multiple sclerosis: A randomized controlled trial - Elahe Baharian; Shahla Abolhassani; Arash Najimi; Fereshteh Ashtari (Journal of Education and Health Promotion)
BACKGROUND: The plethora of troublesome signs and symptoms of multiple sclerosis (MS) reduces patients’ quality of life (QOL) and coping skills. Face-to-face (F2F) education is effective and practical as it allows for more engagement and active learning. The use of mobile health technology to enhance health is now an excellent potential to establish a more efficient health system. The purpose of this study was to determine the effect of a self-care program using two smartphone-based education and F2F education on the QOL and coping skills of people with MS. MATERIALS AND METHODS: This research study was a clinical trial enrolling 60 patients with MS in a hospital in Iran. They were randomly assigned into two groups. The Multiple Sclerosis Impact Scale 29 (MSIS-29) questionnaire and the Multiple Sclerosis Coping Questionnaire (MSCQ) scale were employed to assess the QOL and coping skills, respectively. The training sessions were provided in the form of F2F sessions and an application installed on patients’ mobile phones in the smartphone-based education group. Independent-samples t-test, paired-samples t-test, and chi-square were employed to analyze data via Statistical Package for the Social Sciences (SPSS) software version 20. RESULTS: The results indicated that both F2F and smartphone-based education groups had a significant impact on their mean scores of the QOL (P < 0.001) and coping skills (P < 0.001) pre- and post-intervention. However, there was no significant difference seen between the two educational groups of the QOL (P = 0.23) and coping skills (P = 0.06) post-intervention. DISCUSSION: A comparison of the two groups revealed that both educational methods had the same effect on coping skills and QOL in MS patients. Thus, it can be stated that smartphone-based education can be a good alternative to traditional patient education.